Reconstructing Spiritual Education: A Classical and Contemporary Response to the Mental Health Crisis Among Generation Z from an Islamic Educational Perspective - zulfah zulfah; Nurmadiah Nurmadiah; Makmur Makmur; Umrati Umrati; Husnussadah Husnussadah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
Generation Z's mental health crisis presents a pressing challenge for Islamic education. Classical Muslim scholars developed frameworks of tarbîyah rūḥiyyah (spiritual nurturing) centred on tazkiyat al-nafs, the strengthening of faith, character formation, and iḥsān, yet applying these frameworks to contemporary mental health challenges requires reconstruction rather than mere restatement. This article reconstructs tarbîyah rūḥiyyah by integrating classical literature (al-Ghazālī, Ibn Qayyim al-Jawziyyah, al-Nadwī) with contemporary empirical studies on Islamic spirituality and mental health. The study uses an integrative literature review and hermeneutic engagement with classical texts, synthesizing Scopus- and Sinta 1–2-indexed sources published between 2019 and 2026. Three findings are reported. First, classical Islamic constructs tawakkal, ṣabr, dhikr, and muḥāsabah align closely with empirically documented psychological coping mechanisms. Second, this convergence is not automatic: spiritual education shows statistically non-significant effects on educational quality without adequate pedagogical mediation, and misdirected religiosity can manifest as negative religious coping with pathological consequences. Third, the reconstructed model articulates three interrelated pillars: transcendental-mediated, psychological-hybridized, and ecological-relational, operationalized through five educational implications. The model connects Islamic education with applied Islamic psychology, offering a framework suited to Generation Z's psychosocial profile